Applications of color centers as nanoscopic sensors - Neu, Elke (Elsevier, 2017)
Optically active impurities in diamond, so-called color centers, form versatile sensors: on the one hand, they have demonstrated high sensitivities to temperature, magnetic, and electric fields as well as optical near fields; on the other hand, their atomic size allows for sensing and imaging with potentially nanometer resolution. The chapter introduces the basics of sensing with color centers in diamond with a strong focus on the nitrogen vacancy center in diamond. It also introduces examples of sensing and imaging techniques with color centers including scanning probe imaging. Furthermore, the chapter gives an overview of the use of color centers as highly stable fluorophores in superresolution microscopy.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Magnetometry; Near field imaging; NV center; Scanning probe imaging; Superresolution microscopy